Diffusion of Ideology and Role of Local Party Control to Understand Aceh Post-War - Vellayati Hajad; Susetiawan Susetiawan (Journal of Government and Civil Society, 2022)
AbstractThe purpose of this work are to explore the role of ideological diffusion in the creation and maintenance of GAM 's political hegemony after the Aceh War 2005-2020 and to consider how the practice of command and control were reflected when GAM worked in political parties. The study used a qualitative method with a case study approach and the research data were collected through in-depth interviews with GAM and through journals, books, and articles in print and online. Analysis of this research using data reduction, data presentation, and conclusions/verification. Diffusion of ideology is the main strategy of GAM to win elections by continuing to receive political support from the community. The spread of political ideology were reflected in the behavior of political party, legislative and executive actors, especially when they try to control the management of the government. This research was expected to explain of the use of ideology as a political strategy through the diffusion of ideology in former conflict areas. The diffusion of ideology is a tool used by local political actors as a main strategy for gaining power. By disseminating ideology, the goal is to achieve a situation of hegemony of balance that used as a way to command and control politics. AbstrakTujuan dari penelitian ini adalah untuk menggali peran difusi ideologis dalam penciptaan dan pemeliharaan hegemoni politik GAM pasca Perang Aceh 2005-2020 dan untuk mempertimbangkan bagaimana praktik komando dan kontrol tercermin ketika GAM bekerja di partai politik. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus dan data penelitian dikumpulkan melalui wawancara mendalam dengan GAM dan melalui jurnal, buku, dan artikel baik cetak maupun online. Analisis penelitian ini menggunakan reduksi data, penyajian data, dan penarikan kesimpulan/verifikasi. Difusi ideologi merupakan strategi utama GAM untuk memenangkan pemilu dengan tetap mendapat dukungan politik dari masyarakat. Penyebaran ideologi politik tercermin dalam perilaku para aktor partai politik, legislatif dan eksekutif, terutama ketika mereka mencoba untuk mengontrol pengelolaan pemerintahan. Penelitian ini diharapkan dapat menjelaskan penggunaan ideologi sebagai strategi politik melalui difusi ideologi di daerah bekas konflik. Difusi ideologi merupakan alat yang digunakan oleh aktor politik lokal sebagai strategi utama untuk mendapatkan kekuasaan. Dengan menyebarluaskan ideologi, tujuannya adalah untuk mencapai situasi hegemoni keseimbangan yang digunakan sebagai cara untuk memerintah dan mengontrol politik.